(untitled) (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the analysis of community participation in village fund management in Kampung Mandiri Jaya, Wania District, Mimika Regency. The research method used in this study is a quantitative descriptive research method. The data used in this study are primary data obtained from interviews, observations, questionnaires, and documentation. The analysis technique uses a Likert scale. The results of this study show that the level of community participation in development in Kampung Mandiri can be seen in four areas of participation, namely planning, which scored 84.3 percent or in the very high category; implementation, which scored 86 percent or in the very high category; evaluation/monitoring, which scored 74.4 percent or in the moderate category; and utilization of results, which scored 89.6 percent or in the very high category. The community participation score in development in Kampung Mandiri Jaya is classified as very high, as evidenced by the combined score in the participation field of 83.575 percent. This proves that community participation in development in Kampung Mandiri Jaya is classified as very high.